173k views
2 votes
What is the vertex of f(x)=x^2-6x+3

2 Answers

3 votes

Rearrange into vertex form

x^2 - 6x + 3

= (x - 3)^2 - 9 + 3

= (x - 3)^2 - 6

This is vertex form ( y = a(x - b)^2 + c is general vertex form with vertex

= (b, c) ).

So here the vertex is (3, -6) answer

User Berns
by
5.3k points
6 votes


f(x)=ax^2+bx+c\\\\\text{the vertex}\\\\V(h,\ k)\\\\h=(-b)/(2a),\ k=f(h)

We have:


f(x)=x^2-6x+3\\\\a=1,\ b=-6,\ c=3\\\\h=(-(-6))/(2(1))=(6)/(2)=3\\\\k=f(3)=3^2-6(3)+3=9-18+3=-6

Answer: (3, -6)

User Tyler Pflueger
by
5.6k points